Are Customers Satisfied with Automated Teller Machines Services in Ghana?: A Study of A Universal Bank - Ayimey, Edward Kwame; Awunyo-Vitor, Dadson; Somuah, Richard Oduro (Journal of Asian Business Strategy, 2012)
In a highly competitive industry like banking, one way to gain competitive advantage is to ensure that customers are satisfied and that the services being provided are not flawed with constraints. This study was aimed at finding out if Automated Teller Machines (ATMs), meet the expectations of the customers and what constrained their use by the customers. The study covered five selected branches of a case bank and involved the use of interview guide. In all, 120 respondents were sampled among the customers and 10 from the staff. The data were analyzed using SPSS. From the results, it was realized that the inadequate education given to users of ATMs and the functional limitations identified with the machines were major contributors to customers’ unpleasant experiences at the ATM points. It was recommended that education given to customers on the use of the ATM should be improved and dummy ATMs be installed in the banking halls to facilitate practical training of prospective users.